Gazetteer of General Practices in the Aylesbury Area - Reedy, B. L. E. C. (1973)
One reason for defects in communication between hospitals and general practitioners may be that hospital staff lack information about local practices. We compiled a handbook giving information about 55 (86%) of the practices which use the district general hospital group in Aylesbury. This included biographical details about each doctor in each practice, when he was available on the telephone, what ancillary staff worked in the practice, and so on. The handbook was given to 500 staff in all grades and departments in the group. It seems to have been effective in improving communications, relationships, and morale within the area.